Adaptive multivariable state-space receding horizon control of a turbo-generator pilot plant - Gambier, Adrián; Unbehauen, Heinz (Proceedings of the 35th IEEE Conference on Decision and Control, 2002)
The real-time results of an adaptive multivariable generalized state-space receding horizon control, applied to a turbo-generator pilot plant, are reported in this paper. The control algorithm consists of a state-space receding horizon tracking system, a constant-disturbances compensator and a parameters, state and constant-disturbances estimator based on an augmented bootstrap algorithm. The turbo-generator consisting of a turbine and asynchronous generator exhibits nonlinear and nonminimum phase behaviour in a stochastic environment.
Elektronische Reproduktion der Druckausgbe
Gesehen am 15.01.2020